Waddington Graphics : Publishers of contemporary prints. - Cristea, Alan; Waddington Graphics, London (London : Waddington Galleries, 1986)
Blake, Peter ; Buckley, Stephen ; Caulfield, Patrick ; Dibbets, Jan ; Dine, Jim ; Flanagan, Barry ; Fulton, Hamish ; Hamilton, Richard ; Hoyland, John ; Jones, Allen ; Moon, Mick ; Nicholson, Ben ; Paladino, Mimmo ; Stella, Frank ; Tilson, Joe
biografie, bibliografie
Waddington Graphics : Publishers of contemporary prints, Waddington Graphics, London, 4 June - 12 July 1986
Engels
boek